From Extractive Mining to Green Tourism: A Case Study of Open Pit Nam Salu Geosite Through Local Community Development - Tri Wibowo; Arry Aditsya Yoga; Kharisma Rinandyta (The Journal of Indonesia Sustainable Development Planning, 2024)
Extractive mining has long been central to Belitong Island's economy, particularly tin exploitation since 1908 during the Dutch East Indies period. With Belitong's designation as part of the UNESCO Global Geopark (UGGp), a new opportunity arises to transition toward sustainable economic practices. This research examines the transformation of the Open Pit Nam Salu geosite from a mining-focused economy to an environmentally sustainable green tourism model, emphasizing local community development. Employing a mixed-methods approach, including observations and in-depth interviews with communities and stakeholders, the study explores the geosite's geological and socio-economic potential. It identifies key opportunities and challenges in adopting green tourism while highlighting the critical role of local community involvement in fostering economic resilience. The findings provide a development model that integrates environmental conservation with economic growth. Open Pit Nam Salu's transformation exemplifies how ecological preservation and local economic enhancement can coexist, offering insights for broader application across Indonesia.